2016
DOI: 10.1007/s13205-016-0556-x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and bioactive potentials of culturable heterotrophic bacteria from the surficial sediments of the Arabian Sea

Abstract: Marine sediments accommodate plethora of diverse microorganisms with varying ecological functions. In the present study, we isolated bacteria from surficial sediments of south east Arabian Sea (AS) and evaluated their bioactive potentials. A total of 131 isolates belonging to the phylum: γ-Proteobacteria (63%), Bacillales (34%) and Micrococcaceae (3%) were isolated. Among these, about 40% of the isolates showed the presence of secondary metabolite biosynthetic genes such as PKS or NRPS or both. Organic extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Observations of high degree of microbial diversity in the Arabian Sea [10], [11] led to the hypothesis that the eastern continental slope of Arabian Sea is an enormous source of microbial flora. Microbial diversity of the eastern Arabian Sea has been previously reported [8], [12], [13]. Our study reports the bacterial diversity from the sediments of eastern continental slope of Arabian Sea and their enzyme-producing potential.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Observations of high degree of microbial diversity in the Arabian Sea [10], [11] led to the hypothesis that the eastern continental slope of Arabian Sea is an enormous source of microbial flora. Microbial diversity of the eastern Arabian Sea has been previously reported [8], [12], [13]. Our study reports the bacterial diversity from the sediments of eastern continental slope of Arabian Sea and their enzyme-producing potential.…”
Section: Discussionmentioning
confidence: 68%
“…The continental slope of Arabian Sea is largely unexplored, and may provide a rich source of the potential bacteria capable of producing extracellular hydrolytic enzymes. There are a number of studies reporting marine bacteria capable of producing various extracellular enzymes from different areas of Arabian Sea [6], [7], [8]. Yet, reports are scanty on marine bacteria isolated from sediments of the continental slope of the eastern Arabian Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, early studies in Indian coastal areas revealed that half of the coastal areas are found to be moderate and highly polluted areas by human-activities, coastal urbanization, shipping and aquaculture activities. The influence of pollutions on bacterial diversity were well documented by Ramaiah et al, 1996 , Divya et al, 2010 , Divya et al, 2011 ), Anas et al, (2016) and functional gene diversity in the pelagic and seawater of Indian coastal regions and elsewhere were studied by using classical microbiology approaches ( Woebken et al, 2008 , Ward et al, 2009 , Luke et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…and/or Lysinibacillus spp. displayed high level of bactericidal and cytotoxic properties (Anas et al, 2016).…”
Section: Anti Cancer/cytotoxic Activitymentioning
confidence: 99%